Equilibrium Signal and Purchase Decision in China’s IPO Net Roadshow: A Dynamic Game Approach - Yi Zhao; Dong Li (Discrete Dynamics in Nature and Society)
The net roadshow has been dominant in China’s IPO (initial public offerings) roadshow structure. Considering the dynamic game with incomplete information between the issuer and investor during China’s IPO net roadshow, the quality of the letter of intent is presented as a discrete signal in this paper in accordance with China’s IPO net roadshow characteristics. A signaling game model is established to conclude the issuer’s equilibrium signal and the investor’s purchase action. The issuer disguised a letter of intent to uplift its quality if the disguising cost per share stands below the bidding spread. If the investor judges the letter of intent as high-quality, the basis of purchase is that the opportunity cost per share is less than the expectation on the intrinsic value of the IPO stock. Otherwise the investor rejects purchasing on the condition that the opportunity cost outnumbers the valuation of intrinsic value. In conclusion, there exist unique separating equilibrium and pooling equilibrium as a perfect Bayesian Nash equilibrium, and the existence and uniqueness of their equilibrium domains have been verified by numerical simulation. Finally, the comprehensive empirical studies have validated only one separating and pooling equilibrium existing in China’s real-world IPO market.